Lisfranc Injury Imaging and Surgical Management - Llopis, Eva; Carrascoso, Javier; Iriarte, Inigo; Serrano, Mariano de Prado; Cerezal, Luis (Seminars in Musculoskeletal Radiology, 2016)
The Lisfranc joint is composed of the cuneiform bones and the cuboid and metatarsal bases, united by a synovial capsule and ligamentous complex. Familiarity with the anatomy is essential for image planning and for understanding injury patterns. The more important structures are the Lisfranc ligament and the plantar ligaments that can be visualized with MR, although careful attention to technique and orientation of scan planes is required for accuracy. A combination of conventional radiographs, computed tomography, and MR allow precise diagnosis of Lisfranc fractures, fracture dislocation, and subtle Lisfranc injuries to guide clinical management and surgical planning.
Keywords: Lisfranc; midfoot; fracture dislocation